A1.8 Magnetic Resonance Imaging of Hand and Foot Joints of Patients with ACPA Positive Arthralgia without Clinical Arthritis. (25th February 2013) - Krabben, A; Stomp, W; Heijde, DMFM van der; Nies, JAB van; Bloem, JL; Huizinga, TWJ; Reijnierse, M; van der Helm-van Mil, AHM
Abstract : Background: Anti-citrullinated-peptide antibodies (ACPA) and acute phase reactants are increased before arthritis becomes clinically detectable, suggesting that the processes underlying rheumatoid arthritis (RA) start preclinical. Whether local inflammation occurs in the preclinical phase is unknown. Therefore we studied small joints of ACPA-positive arthralgia-patients on local subclinical inflammation. Methods: Imaging was performed using 1.5T-extremity-MRI. Painful hand or foot joints of 21 ACPA-positive arthralgia-patients without clinical arthritis were imaged. For comparison, hand and foot joints of 22 ACPA-positive RA-patients and of 19 symptom-free controls were studied. Within the ACPA-positive arthralgia-patients painful and symptom-free joint regions were compared. Scoring was performed according to the OMERACT RAMRIS method. Analyses were performed on joint region level and focused on inflammation (synovitis plus bone marrow edoema). Results: The mean combined inflammation-scores of the MCP/ PIP-joints of the controls, the painful joints of ACPA-positive arthralgia-patients and ACPA-positive RA-patients were 0.1, 0.7, 3.7, respectively (p < 0.001). Likewise the mean combined inflammation-scores of the wrist were 0.9, 2.3, 10.3, respectively (p < 0.001) and that of the MTP-joints 0.5, 0.9, 3.8, respectively (p = 0.10). The total RAMRIS-scores of the painful and symptom-free joints within ACPA-positive arthralgia-patients were correlated (rs = 0.61). Conclusions: The present data suggest that local subclinical inflammation occurs in ACPA-positive arthralgia-patients.